Pengaruh Financial Development, Kemajuan Teknologi dan Modal Manusia Terhadap Pertumbuhan Ekonomi ASEAN-8 - Eni Setyo Purwanti; Akhmad Syakir Kurnia (Universitas Diponegoro, 2022)
Economic growth is an indicator of economic performance that is a measure of the success of a country. The 2008 global financial crisis demonstrated the critical role of the financial sector in economic growth. Therefore, this study aims to analyze the effect of financial sector development, technological progress, and human capital on economic growth in 8 ASEAN countries from 2000 to 2019. This study uses secondary data consisting of gross domestic product (GDP), financial development index, gross fixed capital formation (PMTB), individuals using the internet, and education index. The analytical tool used in estimating the regression model in the study is the fixed-effect model with the generalized least square (GLS) method. The results show that financial development has a negative and significant effect on economic growth in 8 ASEAN countries. Meanwhile, technological progress, human capital, PMTB, and the interaction between financial development and PMTB have a positive and significant impact on economic growth in 8 ASEAN countries.